Built to meet needs cultural issues in vernacular architecture - Oliver, Paul (New York Architectural Press, 2006)
The study of vernacular architecture explores the characteristics of domestic buildings in particular regions or localities, and the many social and cultural factors that have contributed to their evolution. In this book, vernacular architecture specialist Paul Oliver brings together a wealth of information that spans over two decades, and the whole globe. Some previously unpublished papers, as well as those only available in hard to find conference proceedings, are brought together in one volume to form a fascinating reference for students and professional architects, as well as all those involved with planning housing schemes in their home countries and overseas.
Keywords: DEFININGTHEFIELD; CULTURESANDCONTEXTS; TRADITIONANDTRANSMISSION; ARCHITECTURE AND ENVIRONMENT (AR-ENV)